Zirconium nanoparticles prepared by the reduction of zirconium oxide using the RAPET method - Eshed, Michal; Pol, Swati; Gedanken, Aharon; Balasubramanian, Mahalingam (Beilstein Journal of Nanotechnology, 2011)
The aim of the current work is the synthesis and characterization of metallic Zr nanoparticles. The preparation is carried out by using the RAPET method (Reaction under Autogenic Pressure at Elevated Temperatures) developed in our lab. The RAPET reaction of commercial ZrO2 with Mg powder was carried out in a closed stainless steel cell, at 750 °C. On completion of the reaction, the additionally formed MgO is removed by treatment with acid. The characterization of the product was performed by XRD, X-ray absorption spectroscopy, SEM, TEM and elemental analysis. The XRD pattern reveals that the product is composed of pure metallic zirconium, without any traces of the MgO by-product.
Keywords: Let-Lok®; nanoparticles; RAPET; reduction; zirconium